Red light and the sleep quality and endurance performance of Chinese female basketball players - Zhao, J.; Tian, Y.; Nie, J.; Xu, J.; Liu, D. (Journal of Athletic Training, 2012)
Context: Good sleep is an important recovery method for prevention and treatment of overtraining in sport practice. Whether sleep is regulated by melatonin after red-light irradiation in athletes is unknown. Objective: To determine the effect of red light on sleep quality and endurance performance of Chinese female basketball players. Design: Cohort study. Setting: Athletic training facility of the Chinese People's Liberation Army and research laboratory of the China Institute of Sport Science. Patients or Other Participants: Twenty athletes of the Chinese People's Liberation Army team (age = 18.60 6 3.60 years) took part in the study. Participants were divided into red-light treatment (n = 10) and placebo (n = 10) groups. Intervention(s): The red-light treatment participants received 30 minutes of irradiation from a red-light therapy instrument every night for 14 days. The placebo group did not receive light illumination. Main Outcome Measure(s): The Pittsburgh Sleep Quality Index (PSQI) questionnaire was completed, serum melatonin was assessed, and 12-minute run was performed at preintervention (baseline) and postintervention (14 days). Results: The 14-day whole-body irradiation with red-light treatment improved the sleep, serum melatonin level, and endurance performance of the elite female basketball players (P < .05). We found a correlation between changes in global Pittsburgh Sleep Quality Index and serum melatonin levels (r = -0.695, P = .006). Conclusions: Our study confirmed the effectiveness of body irradiation with red light in improving the quality of sleep of elite female basketball players and offered a nonpharmacologic and noninvasive therapy to prevent sleep disorders after training.